Anatomical and histochemical characterization of Ayapana triplinervis (Vahl) R. M. King & H. Rob. (Research, Society and Development, 2023)
Anatomical and histochemical characterization of This work aimed to characterize specimens of japana (Ayapana triplinervis) from the medicinal garden of the Federal Rural University of Amazônia - Campus Belém in different types of histochemical tests. Some plants have a large number of varieties, ecotypes and chemotypes, making it difficult to identify them. The photomicrographs in photonic microscopy were obtained from histological slides of the vegetative organs of the root, stem and leaf, made freehand, following the usual techniques of plant anatomy. Histochemical tests were performed using Sudan Black B (Pearse), Lugol (Johansen et al) and Toluidine Blue (O'Brien et al) reagents, for the detection of lipid, starch and acidic polysaccharide compounds, respectively, following the methodology cited in the literature of these authors.